Specific women fears during the СOVID-19 pandemic depending on age and having children - Nefedova, Tetiana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
The COVID-19 pandemic has changed the reality of Ukrainian women. Strong movement restriction, social isolation, the disinclination of the health care system have caused stress and intense emotional fear reaction for their lives and future, future and health of their relatives and children. A survey conducted in the UK has shown that men are more likely to get worse symptoms and die from COVID-19. Other researches, which took place in different countries around the world, have shown that women are more worried, anxious and scared about the consequences of the spread of the coronavirus. The article highlights the actual women’s fears during the COVID-19 pandemic. It analyses the relationship of women’s emotional state to different fears and state/trait anxiety. The aim of the article is to determine the influence of special terms during the COVID-19 pandemic on the intensity of women fears depending on age and having children. Participants (n=140) were asked to complete the Questionnaire of Actual Specific Fears (Ju. Shherbatyh), the Spielberger State-Trait Anxiety Inventory and the visual/verbal analogue fear ‘here and now’ scale. The comparative analysis of two age-band groups has shown that there is no significant difference in the intensity of specific fears and anxiety for 25-44 and 45-60 age groups. It was found that women who have children are rather more worried about not getting ill with some disease, have much higher values of fear ‘here and now’ and fear of heights as opposed to women who do not have children. The present study shows with what fears were women affected by during quarantine restrictions and the spread of the coronavirus. The article emphasizes the importance of the women psychological state, especially women who have children. It is obvious that additional researches are needed; they should explore specific fears connected with children and COVID-19. Further searches are seen in developing a system of psychological support for people who feel fear during the spread of different diseases and new probable pandemics.